The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2014
DOI: 10.1227/neu.0000000000000241
|View full text |Cite
|
Sign up to set email alerts
|

Fifty Consecutive Hemispherectomies

Abstract: Background Techniques for achieving hemispheric disconnection in patients with epilepsy continue to evolve. Objective To review the outcomes of the first 50 hemispherectomy surgeries performed by a single surgeon with an emphasis on outcomes, complications, and how these results led to changes in practice. Methods The first 50 hemispherectomy cases performed by the lead author were identified from a prospectively maintained database. Patient demographics, surgical details, clinical outcomes, and complicati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
0
3

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(22 citation statements)
references
References 56 publications
1
18
0
3
Order By: Relevance
“…A recent systematic review showed that anatomical hemispherectomy had the highest seizure freedom rate, but this was not statistically significant [79]. Reported seizure freedom rates vary significantly between 50% and 85%, with additional patients having significant seizure burden reduction [68,71,73,75,76,[79][80][81][82]. Etiology is the most important prognostic variable of seizure outcome, with acquired and progressive diseases have significantly better outcomes than developmental malformations (particularly hemimegalencephaly) [68][69][70]76,80,83].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A recent systematic review showed that anatomical hemispherectomy had the highest seizure freedom rate, but this was not statistically significant [79]. Reported seizure freedom rates vary significantly between 50% and 85%, with additional patients having significant seizure burden reduction [68,71,73,75,76,[79][80][81][82]. Etiology is the most important prognostic variable of seizure outcome, with acquired and progressive diseases have significantly better outcomes than developmental malformations (particularly hemimegalencephaly) [68][69][70]76,80,83].…”
Section: Discussionmentioning
confidence: 99%
“…While EEG would ideally only show epileptogenicity in one hemisphere, epileptic activity in the contralateral hemisphere is not an absolute contraindication [68,72]. Additionally, hemispherectomy has been rarely described for palliative reduction of seizure burden in bilateral cases [75].…”
Section: Hemispheric Operations 251 Indicationsmentioning
confidence: 99%
“…The modified hemispherectomy also showed good effects on epilepsy control, resulting in Engel I in 91% and Engel II in 9% at follow-up of 7–15 years. In other reports, the rate of seizure freedom following hemispherectomy has been reported to be 52–89%, with a link in improved seizure control and cognitive motor outcomes [ 3 , 9 11 ]. After hemispherectomy, the abnormal waves on EEG on the healthy hemisphere might disappear completely or greatly reduce in the frequency clinically.…”
Section: Discussionmentioning
confidence: 99%
“…Since the introduction of this surgical technique as a therapeutic approach for epilepsy in 1938 [ 4 ], various modifications have been reported to ameliorate the outcome and minimize procedure-related complications [ 4 , 6 8 ]. The rate of seizure freedom following hemispherectomy has been reported to be 52–89%, with a link in improved seizure control and cognitive motor outcomes [ 3 , 9 11 ]. The postoperative mortality rate of hemispherectomy in recent decades has been shown to range from 0 to 1% [ 3 ] or 6.6% [ 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…Extensive clinical experience has established the effectiveness of PIH [10,11], and the efficacy and safety of vertical hemispherotomy have recently been investigated [4,6,12]. In a recent series of 40 cases of vertical hemispherotomy [12], a permanent cerebrospinal fluid shunt was necessary in only 2.5% of cases, compared to the 5-26% incidence in previous series of PIH [10,11]. Blood replacement was necessary in only 2 infants (5.0%) [12].…”
Section: Discussionmentioning
confidence: 99%